2010
DOI: 10.1016/j.ejcts.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of hybrid endovascular repair for thoraco-abdominal aortic aneurysms☆

Abstract: The hybrid TAAA-repair protocol yielded satisfactory results. Although thorough follow-up is required for visceral bypass, this procedure could become the standard for TAAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 22 publications
1
32
0
12
Order By: Relevance
“…A secondary regression analysis of 20 patients in 18 studies who developed irreversible paraplegia 7,8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]29 showed that there was a significant correlation between irreversible paraplegia and death (Pϭ0.002).…”
Section: Spinal Cord Ischemiamentioning
confidence: 99%
“…A secondary regression analysis of 20 patients in 18 studies who developed irreversible paraplegia 7,8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]29 showed that there was a significant correlation between irreversible paraplegia and death (Pϭ0.002).…”
Section: Spinal Cord Ischemiamentioning
confidence: 99%
“…Отсутствуют высокое пережатие аорты [89], перераспределение жидкости [88], декомпрессия задних межреберных артерий (ЗМРА), возникающая при аорто-томии [44], реперфузионное повреждение [3]. Показано, что в этих условиях значительно снижается риск спиналь-ных инсультов, несмотря на протяженное перекрытие ЗМРА, а также радикуло-спинальной артерии Адамкеви-ча (Adamkiewicz) [52].…”
Section: преимущества гибридного вмешательства перед открытымunclassified
“…В межоперационный период может наблюдаться быстрый рост аневризмы, рас-слоение аорты [86] и разрыв аневризмы [22,32,52,57,86,90,92], причем риск зависит от длительности межопера-ционного периода [57,67]. При сроке от 3 до 7 дней пока-зано отсутствие разрывов аневризм [43].…”
Section: выбор стадийной или одномоментной тактики гибридного вмешатеunclassified
See 2 more Smart Citations